Hydrothermal Liquefaction of Mango Seed Kernel to Biocrude Oil and Hydrochar as a Precursor for Biofuel and Chemicals - Stone, A. M.; Garba, K.; Adamu, M. B.; Hammari, A. M. (Darul Yasin Al Sys, 2025)
As the global population grows and conventional resources are rapidly depleted, ensuring energy security and environmental sustainability requires the development of alternative energy sources. High-moisture food waste can be converted into valuable products through hydrothermal liquefaction (HTL), which offers an alternative to traditional waste treatment methods by processing biomass with high moisture content without prior drying, operating at 250–400 °C and 7–10 MPa to produce an energy-dense liquid fuel precursor known as bio-crude oil. This study investigates the thermal decomposition behavior of mango seed kernel (MSK) under batch HTL conditions. The MSK feedstock is characterized by a volatile matter content of 68.71% w/w, fixed carbon of 23.64% w/w, oxygen of 46.13% w/w on a dry basis, and a higher heating value (HHV) of 12.72 MJ/kg. Experiments were conducted at different temperatures (275, 300, and 325 °C) and reaction times (15, 30, and 45 min) at a constant biomass-to-water ratio of 1:7. The maximum bio-oil yield of 27.75 wt% was obtained at 300 °C for 30 min, with carboxylic acids/esters identified as the main compounds in both the light and heavy biocrude oil fractions. The resulting hydrochar exhibited a high carbon content (75–81 wt%), moderate oxygen content (19–24 wt%), and trace amounts of K, Ca, Mg, and P, while FTIR analysis revealed a carbon-rich matrix with oxygenated functionalities (–OH, C=O, and C–O groups) together with aromatic C=C stretches. The study underscores the potential of MSK-derived bio-oil as a precursor for biofuels and biochemicals and highlights the need for further research on harnessing other HTL by-products, such as gases and aqueous organics, for biofuel, biochemical, and related applications.